THE INFLUENCE OF PLANNING, IMPLEMENTATION, AND HUMAN RESOURCES ON THE BUDGET ABSORPTION OF PUBLIC SERVICE AGENCY (BLU) OF TADULAKO UNIVERSITY - Mahardika, Shopia; Djayani Nurdin; Husnah (Master of Management Study Program, Faculty of Economics and Business, Tadulako University, 2023)
This research aims to determine the influence of planning, implementation, and human resources on the budget absorption of the Public Service Agency (BLU) of Tadulako University. The object of this research is the Rectorate of Tadulako University, all Faculties and the Postgraduate Program of Tadulako University. This research was quantitative type using survey methods. Samples were taken through the purposive sampling technique and applied the Structural Equation Model (SEM) method with Variance Based SEM or Partial Least Square (PLS) approach. Hypothesis testing with sig.=0.05. The reliability test applied two criteria: composite reliability and Cronbach's alpa with a coefficient limit value α> 0.70. Data were collected through questionnaires to 52 respondents. The results show that partially the variables of planning, implementation, and human resources have a positive and significant influence on the budget absorption of the Public Service Agency of Tadulako University with p-values >0.001, 0.005, and >0.001, respectively.